Articles sur les rôles des anciens militaires malgaches dans plusieurs régions lors de l’insurrection de 1947-1948 à Madagascar : Avril-Août 1947 - RADANIARISON , Bernardin (Revue Internationale du Chercheur, 2021)
The former Malagasy soldiers who were stranded outside after the Second World War, for lack of material means of trasnport, are back in Madagascar in a particular context. Strikes and demonstrations, alternating with police repression, have affected the country's major centres where ex-combatants pass. Strikes and demonstrations, alternating with police repression, have affected the country's major centres where ex-combatants pass. Since their massive repatriation to Tamatave on August 6, 1946, the former Malagasy miltaires have joined the nationalist cause on which several cities including the capital Antananarivo and the large port of the east coast of Madagascar, are in effervescence. During the insurrection of 1947-1948 they put their military experiences in armed struggle. Moreover, this led to the spread of the insurgency, in the face of which, the actions of the French colonial forces were still limited between April and August 1947. During this period, the former Malagasy soldiers were also very active in the regions of Vohipeno, Farafangana, Fianarantsoa, Manjakandriana and Anjozorobe, Ifanadiana, Mananjary, Nosy varika, Vatomandry, Andevoranto and Brickaville, Tamatave.In time and space, they organized and supervised the insurrection The objective is to show that the former Malagasy soldiers in the insurrection of 1947-1948, wanted the Liberation of their country and the Independence of Madagascar is their leitmotif.